Integrating manufacturing systems through knowledge exchange protocols within an agent-based Knowledge Network - ÖZTEMEL, ERCAN (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Manufacturing enterprises need the ability to respond to rapid changes in the market more than ever before. Besides, they are forced to constantly modify their culture and internal organization structures because of change and intense competition in the market. This obviously requires industrial organizations to manage the different components of their organizations by integrating and coordinating them into a highly efficient, effective, and responsive system in order to maintain and improve their competitiveness. This paper presents a knowledge exchange procedure for creating an integrated intelligent manufacturing system. The basic features of the proposed scheme are introduced and the approach is supported through a case study. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Knowledge exchange; Integrated manufacturing; Knowledge protocols; Manufacturing agents; Knowledge sharing; ARCHITECTURE; METAMORPH